Penguraian Sampah Organik di Bank Sampah Dharma Bakti melalui Budidaya Maggot Black Soldier Fly: Decomposing Organic Waste at the Dharma Bakti Waste Bank through Cultivating Black Soldier Fly Maggots - Yuniar, Risty Jayanti; Gandarrityaz, Rizcky; Aditya, Muhammad Yoga; Valentino, Michael; Siagian, Cindy Tatiana; Kusuma, Muhammad Azi; Farida, Nurul; Fadhillah, Hanifah Nur; Ningsih, Lasti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Dharma Bakti Waste Bank in RT. 55, Muara Rapak Subdistrict, is one of the waste banks that remains active in managing community waste. However, the utilization of organic waste is still limited to compost production, while alternative management methods, such as Black Soldier Fly (BSF) maggot cultivation, have not been optimized. This community service program aims to enhance the utilization of organic waste through BSF maggot cultivation as an alternative feed for livestock, particularly catfish, which are already being farmed by residents. The method used in this program began with an awareness session on the benefits of maggot cultivation, followed by the construction of BSF fly cages, as well as hands-on training and practice on cultivation techniques for residents. The evaluation was conducted by measuring the increase in residents’ understanding before and after the training, along with a community satisfaction survey regarding the activities carried out. The results indicate a 17.98% increase in residents' understanding of BSF maggot cultivation, reflecting the effectiveness of the education and training provided. Additionally, the community satisfaction survey showed that 90% of residents were very satisfied, while the remaining 10% were satisfied. This initiative concludes that, in addition to providing valuable learning experiences for residents, it also empowers them in maggot cultivation through education and training, enabling better optimization of organic waste processing into economically valuable resources.